Evolution of Quality Infrastructure Investment in Japan - Kriss, Paul; Miki-Imoto, Haruka; Nishimaki, Hiroshi; Riku, Takashi (World Bank, Washington, DC, 2021)
This report reviews the evolution of Quality Infrastructure Investments (QII) in the Japanese urban sector. The report is structured around the six QII principles (sustainable development, economic efficiency, environmental considerations, disaster resilience, social considerations and governance) and the three phases of post-war development in Japan. Specifically, the evolution of the six principles is reviewed in relation to historical events during the periods 1956–73, 1974–90, and 1990–2020. The report has the associated case studies for urban practitioners' further read.